2021
DOI: 10.7717/peerj.10887
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals key proteins involved in ethylene-induced adventitious root development in cucumber (Cucumis sativus L.)

Abstract: The mechanisms involved in adventitious root formation reflect the adaptability of plants to the environment. Moreover, the rooting process is regulated by endogenous hormone signals. Ethylene, a signaling hormone molecule, has been shown to play an essential role in the process of root development. In the present study, in order to explore the relationship between the ethylene-induced adventitious rooting process and photosynthesis and energy metabolism, the iTRAQ technique and proteomic analysis were employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…As an important small gaseous molecule, ETH affects the growth and development of plants, and it is also a major regulator in response to diverse stresses. Many studies have shown that ETH can induce adventitious rooting in cucumber and marigold [ 1 , 15 , 16 ]. Using the iTRAQ technique and proteome analysis, Lyu et al [ 16 ] revealed that ETH treatment increased photosynthesis and starch degradation to provide energy for adventitious rooting in cucumber.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As an important small gaseous molecule, ETH affects the growth and development of plants, and it is also a major regulator in response to diverse stresses. Many studies have shown that ETH can induce adventitious rooting in cucumber and marigold [ 1 , 15 , 16 ]. Using the iTRAQ technique and proteome analysis, Lyu et al [ 16 ] revealed that ETH treatment increased photosynthesis and starch degradation to provide energy for adventitious rooting in cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that ETH can induce adventitious rooting in cucumber and marigold [ 1 , 15 , 16 ]. Using the iTRAQ technique and proteome analysis, Lyu et al [ 16 ] revealed that ETH treatment increased photosynthesis and starch degradation to provide energy for adventitious rooting in cucumber. However, some key genes involved in ETH-promoted adventitious root development in cucumber have not been identified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations